Too much or too little? : Disorders of agency on a spectrum - Petrolini, Valentina (Array, 2020)
Disorders of agency could be described as cases where people encounter difficulties in assessing their own degree of responsibility or involvement with respect to a relevant action or event. These disturbances in one’s sense of agency appear to be meaningfully connected with some mental disorders and with some symptoms in particular—i.e. auditory verbal hallucinations, thought insertion, pathological guilt. A deeper understanding of these experiences may thus contribute to better identification and possibly treatment of people affected by such disorders. In this paper I explore disorders of agency to flesh out their phenomenology in more detail as well as to introduce some theoretical distinctions between them. Specifically, I argue that we may better understand disorders of agency by characterizing them as dimensional. In §1 I explore the cases of Auditory Verbal Hallucinations (AVH) and pathological guilt and I show that they lie at opposite ends of the agency spectrum (i.e. hypoagency versus hyperagency). In §2 I focus on two intermediate cases of hypo- and hyper- agency. These are situations that, despite being very similar to pathological ones, may be successfully distinguished from them in virtue of quantitative factors (e.g. duration, frequency, intensity). I first explore the phenomenon of mind wandering as an example of hypoagency, and I then discuss the phenomenon of false confessions as an example of hyperagency. While cases of hypoagency exemplify situations where people experience their own thoughts, bodies, or actions as something beyond their control, experiences of hyperagency provide an illusory sense of control over actions or events.